Transition to Adult IBD Care: A Pilot Multi-Site, Telehealth Hybrid Intervention. (24th November 2020) - Gray, Wendy N; Wagoner, Scott T; Schaefer, Megan R; Reed, Bonney; Morgan, Pamela; Holbrook, Erin; Yacyshyn, Bruce; Mackner, Laura; Young, Margaret; Maddux, Michele; Saeed, Shehzad A; Denson, Lee A; et al.
Abstract: Objective : Transition to adult IBD care continues to be a challenge. Efficacious models of improving transition to adult care in the United States are lacking. We present data from a pilot, prospective, non-randomized, intervention implemented at IBD centers in the Midwest and Southeast United States. Design and Methods : Adolescents and young adults (AYAs; 16–20 years) with IBD and their parents completed a 4- to 5-month transition program (1 in-person group session; 4 individual telehealth sessions). Primary outcomes were feasibility (i.e., recruitment, retention, fidelity) and acceptability (i.e., program satisfaction). Secondary outcomes were changes in transition readiness, self-management skill acquisition, perceived readiness to transfer to adult care, and disease knowledge. Results : The study exceeded goals for recruitment (target N  = 20; actual: 36) and retention (target: 80%; actual: 86.11%). On average, it took participants 20.91 ± 3.15 weeks to complete our 4- to 5-month intervention and there were no deviations from the study protocol. Participant ratings for overall program satisfaction, perceived helpfulness, and program length and format were positive. Increases in transition readiness, t (30) = 8.30, d  = 1.49, p < .001, self-management skill acquisition, t (30) = 3.93, d  = 0.70, p < .001, and disease knowledge, t (30) = 8.20, d  = 1.58, p < .001 were noted. AYA- and parent-perceived transfer readiness also improved ( p 's < .05; d 's = 0.76–1.68). Conclusions : This article presents feasibility and acceptability data for a 4- to 5-month transition intervention. Improvements in AYA transition readiness, self-management skill acquisition, IBD knowledge, and AYA/parent perceived transfer readiness were also observed.